Collegiate Millennials' Perceptions of Locally Produced Beef - Shelby Oesterreicher; Lisa K Lundy; Joy N Rumble; Ricky W Telg (Journal of Applied Communications, 2018)
Millennial consumers are stepping into important roles as decision makers and consumers. A knowledge and communication gap exists between cattle producers and consumers this knowledge seeking generation. This study focused on collegiate millennials’ perceptions of locally produced beef. The research design was qualitative in nature using focus groups. Participants associated the beef industry and beef products with the environment, management practices, treatment of animals, human health concerns, retail, experience with the beef industry, experience with beef, and transparency. Results of this study showed participants had minimal knowledge of the industry and relatively negative perceptions of the industry and beef products. Participants were skeptical of communication materials promotion beef and expressed particular distrust toward video messages. Participants revealed a knowledge and communication gap between producers and consumers.
Keywords: perceptions; local; beef; focus groups; consumer perceptions